CYBER VICTIMIZATION OF THE ELDERLY - Sarmart, Thanpitcha; Lerdtomornsakul, Unisa (Thai Interdisciplinary and Sustainability Review, 2023)
The purpose of this study was to investigate the reasons why older people become victims of cyber scams and to study patterns of victimization of cyber scams. This research is qualitative research using in-depth interviews with 24 elderly who are victims of cyber scams, 5 people involved in the scam, and 8 staff and academics involved in rescue or prevention. According to the findings, the elderly victims were divided into 4 groups which are 1) victims of investment scams with the characteristics of high returns as incentives 2) victims of call center gangs which is usually a form of deception to create panic, greed, or pretend to be an acquaintance 3) victims of online shopping scammers, who create a profile that looks credible, and fraudulent products are often low-priced and 4) the elderly people who fall victim to online romance scams. Scammers use psychology to deceive the elderly to fall in love before leading to the scam of money. The reasons for falling victim to scams differ for each form of cyber scam.